Programming PHP - Lerdorf, Rasmus (O'Reilly, 2006)
Programming PHP, 2nd Edition, is the authoritative guide to PHP 5 and is filled with the unique knowledge of the creator of PHP (Rasmus Lerdorf) and other PHP experts. When it comes to creating websites, the PHP scripting language is truly a red-hot property. In fact, PHP is currently used on more than 19 million websites, surpassing Microsoft's ASP .NET technology in popularity. Programmers love its flexibility and speed; designers love its accessibility and convenience. As the industry standard book on PHP, all of the essentials are covered in a clear and concise manner. Language syntax a.